THE EFFECT OF EMULSIFIER SPAN 60 (Sorbitan Monostearate) ON THE HOMOGENEITY PROPERTIES OF LOTION GEL MADE Virgin Coconut Oil (VCO) AND ALOE VERA - Nurhaliza, Siti; Yunus, M; Adriana, A (Jurnal Sains dan Teknologi Reaksi, 2023)
ABSTRACT Making lotion from Virgin Coconut Oil (VCO) and Aloe Vera to which an emulsifier has been added requires antimicrobial ingredients, because the water phase facilitates the growth of microorganisms. The presence of methyl paraben preservative is very important in oil-in-water emulsions, because the shelf life of the product will last longer. This research aims to determine the effect of span 60 on homogeneity properties. The physical properties of the lotion include homogeneity test, pH test, viscosity test and specific gravity test based on SNI-16-3499-1996. The experimental process was carried out with varying weights of span 60 (sorbitan monostearate) 1 mg, 3 mg, 5 mg, 7 mg, methyl paraben with varying weights of 1.5 mg, 2 mg, 2.5 mg, 3 mg and a stirring time of 21 minutes. With the liquid phase and the heated oil phase.0.95- 1.05 g/ml. Keywords: Virgin Coconut Oil (VCO), Aloe Vera, Emulsifier, Span 60 (Sorbitan Monostearate), Methyl Paraben, Homogeneity.